Food Supply Security and Import Substitution as the Key Strategic Objectives of the Modern Agricultural Policy - Altukhov, Anatoly Ivanovich; Drokin, Veniamin Vasilyevich; Zhuravlev, Alexey Serafimovich (Economy of Regions, 2015)
A crucially new social- and economic situation has shaped up by now in the rural areas and agricultural sphere; in its many instances such situation does not fit in the national agricultural policy in effect called upon to be a long-term instrument for economic adjustment of the agro-food market and state support of the agricultural sphere, most significantly, its foundation - the farming sector. Ensuring of food supply security by import substitution in the age of the national farm product markets globalization is possible in the macro-economic conditions promoting the development of the agricultural sector. The main reason that retards this sector development is inequitable cross-sector exchange at sacrifice of the agricultural industry. The article sets forward and approbates the author's method of simple assessment procedure of how the price cross-sector relations and state financial support (in the form of subsidies) of the agricultural enterprises influence their profitability generation. Further to the assessment, the following conclusions have been made: - in view of the tangible contribution of the agricultural sector to the country economy, this sector is self-reliant for its own development, i.e. the state is reasonably in a position to increase expenses for eliminating negative consequences of inequitable crosssector exchange; - the amount of expenses for state financial support is supposed to enable the agricultural commodity producers to generate profitability to the level that can stimulate the farm workers' labour efficiency and build up a system of affordable credit facilities for the objects of techno-engineering modernization necessary to produce competitive products. - the issue of improving the competitiveness of agricultural production should be addressed in the first place at the federal level. Among the essential factors to increase the competitiveness of specific types of domestic food products and agricultural raw materials, one should consider the implementation of theoretically sustained agreements on the agricultural policy in EEU countries. The article considers the guidelines to form the common agricultural policy in the new integrated entity.